Challenges in open distance learning (ODL): an exploratory study on pandemic era quantity surveying graduates - Yusni, Afiq Imran; Azman, Mohd Azrai; Abd Rashid, Ahmad Faiz; Mahat, Noorsaidi; Mat Nasir, Nasyairi; A. Rahman, Rahimi (UiTM Press, 2025)
The need to maintain educational continuity during the COVID-19 pandemic has accelerated the adoption of Open Distance Learning (ODL). However, whether ODL can adequately prepare graduates from technical disciplines, such as Quantity Surveying (QS), for industry demands has not been verified in detail. In response, this study investigates employer perceptions of QS graduates trained through ad hoc Open Distance Learning (ODL), a mode of education widely adopted during the COVID19 pandemic. The objectives are to assess employers' views on the performance of these ODL graduates, evaluate the effectiveness of ODL in preparing QS graduates for employability, and identify strategies to improve the alignment of ODL implementations with employer expectations. Data were collected using a structured questionnaire survey from 71 employers in the Malaysian construction industry in Selangor and analysed using descriptive statistics, Cronbach’s alpha to assess reliability, and the Kruskal-Wallis’s test to identify differences in employer perceptions. The findings reveal mixed perceptions. While some employers appreciated the knowledge and general understanding of ODL graduates, concerns were raised regarding their technical skills, ability to meet industry demands, and proficiency in using industry-specific tools. Employers also highlighted gaps in teamwork, communication, and the overall readiness of graduates to handle real-world challenges. Scepticism remains regarding the alignment of ODL programs with practical industry needs.